An Industrial quality control study on IDS Logistics (Involving Unilever Food Solutions Products) - Guarin, Andrei; Jalao, Eugene Rex.; Quizon, Janine Lei.; Ulpindo, Christopher Ian. (Diliman, Quezon City College of Engineering, 2006)
In order to apply the statistical process control methods learned in IE 135, the group undertook a study on a company with certain methods and processes that needed to be monitored. Unilever Foods (formerly known as California Manufacturing Company or CMC), an already-established company in the Philippines, was chosen as the site, and the group was assigned to wkr specifically on the product lines of Best Foods Say Cheez and Lady's Choice Mayonnaise. These products are manufactured in Unilever's main plant located in Gateway Industrial Park in General Trias, Cavite, and thus the company relies on Integrated Distribution Systems (IDS) Logistics for its transportation and warehousing needs. In order to monitor the transportation of goos from plant to warehouse, both Unilever and IDS use what are called Stock Transfer Documents (STDs) and Short-Overlanded Advices (SOAs). The STDs contain information regarding the quantity as well as the descriptions of the products to be delivered (i.e. Best Before/BB dates and pallet number). the SOAs on the other hand, are used when products that are delivered and inspected either a) Do not match the description in the documents or b) are damaged and are damaged and therefore not counted as delivered in good condition. Upon the arrival of the goods in the Libis warehouse, IDS personnel perform 100 percent inspection on each pallet delivered. SOAs are then filled up and forwarded to the office where these forms are then documented. The data collected from seventeen weeks of deliveries (from May to September of 2005) were used by the group in order to analyze the reception process of IDS. IDS personnel classify problems with deliveries and indicate these in the SOAs according to these categories: A. Damaged Cartons B. Collapsed/Crushed Cartons C. Wet Cartons D. Product Leakages E. Oil Sep (mayo) F. Wrong BB. Dates G. No Labels in pallets/cartons. The group chose to utilize the P attributes control chart, since no measurement is involved in inspecting the products; these are only observed as in good condition (conforming) and damaged or with discrepancies (non-conforming).
Analyzing the data gathered, it can be seen that the 5 problems classified in the SOAs indeed pose a problem for both IDS and Unilever, since these consistently interrupt the flow of products from the principal (Unilever) to the warehouse (IDS) and to the clients. Asie from incurring time/production delays due to product repacking, re-labelling and complete product replacement, the company also incurs additional costs with regards to manpower and material. With regards to the problems of damaged cartons, collapsed cartons and wet cartons, these can be traced to the trucks involved and driver handling. Since one hundred percent inspection is done as well on the pallets (Unilever personnel) before the products leave the gateway plant, the damages incurred by the cartons are traced to in-transit reasons. Product leakages can be attributed to product packaging within the Unilever compound since packaging for each variant is designed such that leakages during product transport are minimized eliminated. Oil separations happen when too much heat is absorbed by the mayonnaise package, causing the product oil to separate from the other ingredients. Damaged cartons were found to be the most prominent problem among the 6 nonconformities, and it can also be observed that 5 out of these 6 cans can be classified as due to physical occurrences on the cartons/pallets. Proper loading and securing of these products during transport are key preventive measures by which the number of nonconforming arrivals can be reduced. The group recommended that either a full plastic cover or a tarpaulin cover on the products, as well as serve as shield from rainwater seeping into the truck's cargo area. A time study was also recommended by the group to be conducted on Unilever's packaging area will mean reduced exposure time, and will in turn lessen the risk of damage and of oil separations (especially in the case of the 3.55L variants.
IE 135
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: IDS Logistics; Food industry; Quality control